Micro, Small and Medium Enterprise Strategies for Women in Facing Competition in Bacukiki District, Parepare City - Dewintara, Eka; Aminah, St.; Semaun, Syahriyah; Muliati, Muliati; S, Andi Bahri (Jurnal Ekonomi Balance, 2024)
This research discusses the strategies of women's micro, small and medium enterprises in facing competition in Bacukiki sub-district, Parepare city. This research is descriptive qualitative research with a type of field research, phenomenological research approach. The main problem in this research is how women's micro, small and medium enterprises face competition in Bacukiki sub-district, Parepare city. It was found that women in micro, small and medium enterprises in the Bacukiki subdistrict of Parepare city had high motivation in running their businesses. It can be seen that women run businesses because of their hobbies, dreams of owning a business and becoming successful entrepreneurs and wanting to help the family economically. The steps taken by women so that their business continues to run as desired are that they carry out regular evaluations, both monthly and weekly evaluations, then seek more knowledge about the business they are running so that their business can develop further, and they determine their target market, carry out planning and provide promotions or discounts to consumers.